Digitalization of tourist attractions: Increasing the capacity of Sunrise Land Lombok tourism workers through digital marketing - Sheidy Yudhiasta; Joko Mijiarto (Journal of Community Service and Empowerment, 2023)
The Covid-19 pandemic has driven changes in various fields in the application of technology, including in the tourism sector. Increasing the use of social media is a new challenge for tourism workers to carry out digital marketing. However, human resources capable of using technology and conducting digital marketing in tourism management are not always available. The purpose of this community service is to improve the quality and ability of Sunrise Land Lombok (SLL) employees to digitize and use social media. The implementation of community service will be carried out from October to December 2022 by providing training and assistance SLL tourism workers. The stages carried out in this service include the stages of observation and interviews, training, mentoring, and evaluation. Based on observations and interviews with the director of SLL, it is known that SLL workers face several obstacles in utilizing social media. These obstacles include more understanding about creating engaging social media content. Based on these problems, the training materials provided include: 1) Content planning, Canva, and website training for scheduled posting; 2) Press release writing and copywriting training and 3) practice video editing using CapCut and VN. The training is carried out online and is divided into several meetings, with each meeting accompanied by assignments for workers to practice the material given during the delivery.